2017
DOI: 10.1126/scisignal.aag1775
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by two-component system noncognate partners promotes intrinsic tolerance to polymyxin B in uropathogenic Escherichia coli

Abstract: Bacteria use two-component systems (TCSs) to react appropriately to environmental stimuli. Typical TCSs comprise a sensor histidine kinase that acts as a receptor coupled to a partner response regulator that coordinates changes in bacterial behavior, often through its activity as a transcriptional regulator. TCS interactions are typically confined to cognate pairs of histidine kinases and response regulators. We describe two distinct TCSs in uropathogenic Escherichia coli (UPEC) that interact to mediate a resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 58 publications
8
54
0
Order By: Relevance
“…The same studies also elucidated that phosphorylated PmrA (PmrAϳP) and QseB (QseBϳP) coregulate downstream targets, which in Salmonella spp. are exclusively controlled by PmrA (11). Together, these studies provided evidence of two TCSs, whose partner proteins interact to mediate a particular response.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…The same studies also elucidated that phosphorylated PmrA (PmrAϳP) and QseB (QseBϳP) coregulate downstream targets, which in Salmonella spp. are exclusively controlled by PmrA (11). Together, these studies provided evidence of two TCSs, whose partner proteins interact to mediate a particular response.…”
mentioning
confidence: 81%
“…In the absence of QseC, QseBϳP binds and induces the expression of qseBC, resulting in increased levels of qseB steady-state transcript (11,12,15). Quantitative PCR (qPCR) analysis demonstrated that introduction of the mutated qseC sequences suppressed the aberrant expression of qseB (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations